Consistency of passerine embryo development and the use of embryonic staging in studies of hatching failure. (16th December 2015) - Hemmings, Nicola; Birkhead, Tim R.
Abstract : Hatching failure is widespread in birds, and is usually the result of embryo death rather than infertility. Embryo death can result from both intrinsic and extrinsic factors, some of which may vary across the developmental period. Determining the point at which an embryo died during development may therefore help us to understand the underlying cause of death. Here we describe simple criteria that can be used by field ornithologists to establish the developmental stage of dead embryos found in unhatched passerine eggs, and explain how this can be used to estimate the date of embryo death. We compared the pattern of embryo development over the incubation period for three species, the Zebra Finch Taeniopygia guttata, Blue Tit Cyanistes caeruleus and Great Tit Parus major . We also compared rates of Zebra Finch embryo development under artificial and standard (parental) incubation. Embryo development rates were remarkably similar across the three species and between Zebra Finch embryos under artificial and natural incubation conditions. We therefore suggest that the pattern of embryo development in the Zebra Finch may provide a model for other small passerines with similar incubation periods, but acknowledge that further interspecific comparisons are required before this model is considered more widely applicable. By estimating embryo death dates using our approach, ornithologists will be able to determine temporal patterns of embryo mortality in relation to extrinsic environmental conditions. This approach may shed light on how extrinsic factors such as climate and parental behaviour influence embryo survival in wild birds.